Constitution of India (New Delhi Mythoria Press, 2024)
The Constitution was framed by the Constituent Assembly of India, established by the members of the provincial assemblies elected by the people of India. Dr. Sachidanand Sinha was the first president of the Constituent Assembly. Later, Dr. Rajendra Prasad was elected its president. Dr. B.R. Ambedkar, the chairman of its Drafting Committee, is considered the chief architect of the Indian Constitution, which provides a comprehensive and dynamic framework to guide and govern the country, keeping in view its unique social, cultural, and religious diversity.
Keywords: Governance Sector; Constitution- India